On the Need And Ways of Converting Some of the Components of Goodwill Into Identifiable Intangible Assets - M.E.Pulatov (Universitas Muhammadiyah Sidoarjo, 2019)
This article justifies the need and ways to transfer some types of exclusive rights from goodwill to identifiable intangible assets. On this way, case of national accounting system and theoretical background of the topic were discussed. Moreover, practical issues and literature review of the different point mentioned on the methodology. Finally, research concludes major points in order to make further development as the whole.